Screening algorithms for detecting dysphagia: A validation study of Thai EAT-10 combined with the 3-Ounce Water Swallow Test - Kongma, Pilaiwan; Korwanich, Narumanas; Klibngern, Hanpon; Tavisak, Natchaiyant; Inoue, Makoto; Korwanich, Kanyarat (Journal of Associated Medical Sciences, 2023)
Background: Dysphagia assessment using standard tools is not commonly performed in Thailand because it relies on equipment and experts to evaluate. This study was conducted by combining the Thai EAT-10 and the 3-ounce water swallow test, an easy-to-use tool for dysphagia screening. Therefore, it is crucial to study the accuracy and appropriateness before being widely used in the Thai population. Objectives: To evaluate the validity of the combined Thai Eating Assessment Tool 10 (Thai EAT-10) and the 3-ounce Water Swallow Test (WST) screening algorithm for detecting dysphagia compared to diagnosis by an otolaryngologist. Materials and methods: Analytical Cross-sectional study: sample of 260 adults (aged 20 years old or older) demographic data and past medical history were assessed using a questionnaire. The accuracy of dysphagia screening tests that combine Thai EAT-10 and the 3-ounce water swallow test with pulse oximetry was compared to the clinical swallow test assessed by an otolaryngologist. The sensitivity and specificity of the swallowing screening test for detecting dysphagia were evaluated. Results: Thai EAT-10 combined with the 3-ounce Water Swallow Test has higher validity and accuracy for dysphagia evaluation than those of the Thai EAT-10 or the 3-ounce Water Swallow Test alone. There was 100% sensitivity, 93.4% specificity, 68.1% positive predictive value (PPV), and 100% negative predictive value (NPV). Conclusion: The Thai EAT-10 combined with the 3-ounce water swallow test and pulse oximetry has higher reliability and validity than those of the Thai EAT-10 and the 3-ounce water swallow test alone. The reliability and validity of the combined test is closed to the gold standard. Furthermore, the algorithm is appropriate for screening dysphagia in remote areas with a large population.